Nurses' Perspective on Caring for Women Experiencing Perinatal Loss. Issue 1 (January 2019) - Willis, Patricia
Abstract: Purpose: The purpose of this study was to describe the experience of caring for women with a perinatal loss from the perspective of the nurse and to determine the extent to which the response to perinatal loss reflects a process. Study Design and Methods: A purposive study was conducted with nine labor and birth nurses with experience in caring for women with a perinatal loss. The nurses were from two acute care hospitals within one healthcare system in Southeastern Massachusetts. A qualitative descriptive design with in-depth interviewing based onRubin and Rubin (2012) was used to gather and analyze data. Results: Several themes depicting nurses' experience were identified: struggling with emotions, carrying on in the moment, being present for the patient, expressing conflict, and taking care of self. A process was identified by nurses describing their response to perinatal loss. The process began with recognition of the loss and progressed through phases including the recognition of their emotional impact, connecting with the mother, dealing with emotions, acting professionally, preparing to return to work, and never forgetting the woman. Clinical Implications: Nurses identified a need for more education and managerial support for excellence in care of women with a perinatal loss. Education to prepare nurses to meet the physical, psychological, and spiritual needs of women is recommended. Debriefing after caring for a woman with a loss was suggested by the nurses. When nurses' needs are met, they are better prepared to care for women experiencing a perinatal loss. Abstract : In this study, labor and birth nurses offer their perspectives on caring for women experiencing a perinatal loss and identify specific strategies that have the potential to enhance their ability to provide their best care.